Psikoedukasi Manajemen Stres sebagai Upaya Peningkatan Kesejahteraan Mental Ibu Rumah Tangga - Putri Luthfia Nazhiifah; Rani Saptya -Ramadhani; Dewi Qurrotul Aini; Abdul Muhid (FKIP Universitas Mataram, 2026)
Housewives with dual roles are included in the vulnerable group because they face economic pressure, lack of social support, and household burdens that trigger prolonged stress. This empowerment program aims to improve the mental well-being of housewives thru psychoeducation on stress management and expressive writing training. This activity uses the Participatory Action Research (PAR) approach, which includes the stages of planning, action, observation, and reflection. The participants consisted of 15 housewives in the Gunung Anyar area. Data were collected thru pre-test, expressive writing, post-test, and documentation, and then analyzed qualitatively. The results show an increase in participants' understanding of the concept of stress, sources of stress, and its signs, as well as changes in the way they manage stress more adaptively. This program also strengthens the ability to reflect on emotions and self-control as part of the psychological empowerment process for housewives.